Performance of the reinforced concrete beam with arch shaped tension steel bar - Mangaibagan, Rajandran (2016)
Reinforced concrete beams are designed to resist compressive force and tensile force resulting from various combinations of ultimate loads. In the design of reinforced concrete beam, the effect of flexural tensile stresses needs to be considered as they contribute to flexural failure such as deflection and cracking. A study was conducted in the laboratory to investigate the performance, in term of ultimate load deflection ratio, of simply supported reinforced concrete beam with different arch height and angle of the steel bar in tension zone. Four reinforced concrete beams was casted with same concrete grade of 31.9Mpa and area of steel bar but with different arrangement of longitudinal steel bar in tension zone where one is control sample and the other three are modified sample. Each beam was design in accordance with Eurocode 2 and with dimensions 2000mm x 200mm x 150mm. All specimens underwent laboratory testing with loading as one point load onto the centre of beam with support at each corner of the specimens. The specimens were tested until failure. The result of the test emphasize that the ultimate load and deflection of simply supported reinforced concrete beam is influenced by the arch shaped steel bar with different arch angle and height in tension zone. Moreover, the result implies that all the specimens show only major flexural failure where vertical cracks happen at the middle part of specimens. It can be concluded that among the entire simply supported reinforced concrete beam with different arch angle and height of steel bar in tension zone, Specimen 2 shows the optimal ratio of ultimate load over deflection which is 2.950.